Pengaruh Organizational Citizenship Behavior Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PT. Tifico Fiber Indonesia Tbk Departemen Polymer - Bilal Achmad Baihaq; Derita Qurbani (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. The purpose of this study is to determine the partial and simultaneous influence of organizational citizenship behavior and the physical work environment on employee performance at PT Tifico Fiber Indonesia Tbk, Polymer Department. This research employs an associative method. The population in this study consists of all employees in the Polymer Department, while the sample used comprises 134 respondents. The data collection technique used was a questionnaire, and data analysis techniques included instrument testing, classical assumption testing, regression analysis, correlation coefficient, coefficient of determination, t-test, and F-test. The results of the study indicate that: (1) Organizational Citizenship Behavior has a positive and significant effect on employee performance, as shown by the tcount value of 14.346 > ttable 1.978 with a significance level of 0.001 < 0.05 (2) the physical work environment has a positive and significant effect on employee performance, indicated by the tcount value of 13.635 > ttable 1.978 with a significance level of 0.001 < 0.05 (3) Organizational Citizenship Behavior and the physical work environment simultaneously have a positive and significant effect on employee performance, as evidenced by the Fcount value of 162.462 > Ftable 3.07 with a significance level of 0.001 < 0.05g Keywords: Organizational Citizenship Behavior, Physical Work Environment, Employee Performance